CP violation in rare lepton-number-violating W decays at the LHC - Fatemeh Najafi (Journal of High Energy Physics, 2021)
Abstract Some models of leptogenesis involve a quasi-degenerate pair of heavy neutrinos N 1,2 whose masses can be small, O(GeV). Such neutrinos can contribute to the rare lepton-number-violating (LNV) decay W ± → ℓ 1 ± ℓ 2 ± q ′ q ¯ ∓ $$ W^{±}→ {\mathrm{\ell}}_1^{± }{\mathrm{\ell}}_2^{± }{\left({q}^{′}\overline{q}\right)}^{\mp } $$ . If both N 1 and N 2 contribute, there can be a CP-violating rate difference between the LNV decay of a W − and its CP-conjugate decay. In this paper, we examine the prospects for measuring such a CP asymmetry ACP at the LHC. We assume a value for the heavy-light neutrino mixing parameter |B ℓN |2 = 10 −5, which is allowed by the present experimental constraints, and consider 5 GeV ≤ M N ≤ 80 GeV. We consider three versions of the LHC — HL-LHC, HE-LHC, FCC-hh — and show that small values of the CP asymmetry can be measured at 3σ, in the range 1% ≲ A CP ≲ 15%.